2022
DOI: 10.33448/rsd-v11i16.37920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of using activated carbon and graphene oxide on the microwave assisted pyrolysis of expanded polystyrene waste

Abstract: Polymers are increasingly present in everyday life to replace other materials. Because they are cheap and have attractive mechanical properties, they were and still are produced on a large scale and, consequently, their large volumes in landfills present a challenge for their recycling. Thus, the objective of this study was to evaluate the depolymerization of expanded polystyrene (EPS) waste through the use of microwaves using two agents that have carbon in their constitution to assist in depolymerization: gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Their studies revealed that there was an optimum oil yield of 93% at a microwave of 450W and polymer to activated carbon ratio of 10:1 which was conducted at a temperature of 330 0 C for 5.5 minutes. A typical microwaveassisted pyrolysis set-up for expanded polystyrene is shown in figure 3 below Figure 5 Microwave-assisted pyrolysis of EPS waste set-up (source: [53]) Additionally, Zancanaro, Poletto [54] reported the depolymerization of expanded polystyrene waste using graphene oxide and activated carbon catalysts via microwave-assisted pyrolysis. They varied the quantity of the catalysts being used from 0.125, 0.25, and 0.5g.…”
Section: Thermal Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Their studies revealed that there was an optimum oil yield of 93% at a microwave of 450W and polymer to activated carbon ratio of 10:1 which was conducted at a temperature of 330 0 C for 5.5 minutes. A typical microwaveassisted pyrolysis set-up for expanded polystyrene is shown in figure 3 below Figure 5 Microwave-assisted pyrolysis of EPS waste set-up (source: [53]) Additionally, Zancanaro, Poletto [54] reported the depolymerization of expanded polystyrene waste using graphene oxide and activated carbon catalysts via microwave-assisted pyrolysis. They varied the quantity of the catalysts being used from 0.125, 0.25, and 0.5g.…”
Section: Thermal Recyclingmentioning
confidence: 99%
“…That notwithstanding, researchers pointed out that depolymerization time, type of catalyst, and temperature play a crucial role in determining the quality and quantity of polymer yield in the process [53]. Also, another important parameter which plays a vital in promoting expanded polystyrene waste depolymerization is using material components that have high thermal conductivity like metals or carbonaceous compounds [54]. According to Bartoli, Rosi [55], these components can enhance heat transfer by absorbing electromagnetic waves and transmitting them to the polymer during the pyrolysis process.…”
Section: Thermal Recyclingmentioning
confidence: 99%